FAHM AL-QUR’AN AL-HAKIM; TAFSIR KRONOLOGIS ALA MUHAMMAD ABID AL-JABIRI - Wardatun Nadhiroh (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
In general, most of Qur’anic interpretations (Kitab-kitab Tafsir, red-) have a systematic of Qur’anic order in Mushaf, started from Surah al-Fâtihah and ended at Surah al-Nâs. Unlike those, Muhammad Abid al-Jabiri, is commonly known as al-Jabiri, contemporary Islamic thinker from Marroco, wrote a Qur’anic interpretation based on chronological order of Surahs, Fahm al-Qur’ân al-Hâkim. It is started from Surah al-Alaq: 1-5 and ended at Surah al-Nashr. Al-Jabiri offered new methodology to understand Qur’anic text which he called as al-fashl to answer problems of objectivity and al-washl to answer problems of rasionality. He based his interpretation on Qirâ’ah Muâshirah (contemporary reading) so Qur’anic text will be contemporary for itself and contemporary for its readers in contemporary context. This article describes briefly about al-Jabiri’s works, Fahm al-Qur’ân al-Hâkim, his thoughts in Qur’anic issues and his offered interpretation methodology.